Serum Leptin and Adiponectin Levels in Obese and Nonobese Asthmatic School Children in relation to Asthma Control. (17th December 2013) - Abdul Wahab, Atqah; Maarafiya, Muna M.; Soliman, Ashraf; Younes, Noura B. M.; Chandra, Prem
Abstract : There is growing evidence of a positive correlation between asthma and obesity in children and adults. Leptin and adiponectin regulate several metabolic and inflammatory functions. This study aims to evaluate serum leptin and adiponectin concentrations in asthmatic school children to investigate their association with obesity and the degree of asthma control. Obese asthmatic (OA) and nonobese asthmatic (NOA) children, aged 7 to 14, were randomly enrolled in this prospective study. Data on demographic, anthropometric, serum lipids, and spirometric measures and allergy status were collected and analyzed. Serum leptin was significantly higher (25.8 ± 11.1 versus 8.7 ± 11.1 ; P < 0.0001 ) and adiponectin levels were lower (2.5 ± 1.2 versus 5.4 ± 2.9 ; P < 0.0001 ) in OA compared to NOA children. The uncontrolled group had higher leptin and lower adiponectin levels compared to well and partially controlled asthma. BMI was positively correlated with leptin (r = 0.79 ; P < 0.001 ) and negatively with adiponectin (r = - 0.73 ; P < 0.001 ). Mean BMI and leptin levels were observed to be higher in girls compared to boys. Stepwise multiple linear regression analysis showed that higher BMI and female gender had significant effect on serum leptin levels. Among asthmatic children higher serum leptin and lower adiponectin levels were significantly associated with obesity and showed no significant association with degree of asthma controls.